Evaluating Cultural Ecosystem Services of Urban Residential Green Spaces From the Perspective of Residents' Satisfaction With Green Space - Mao, Qizheng; Wang, Luyu; Guo, Qinghai; Li, Yuanzheng; Liu, Min; Xu, Guanghua (Frontiers in public health, 2020)
Green spaces in residential areas provide multiple cultural ecosystem services (CES), which can contribute to human health by increasing the frequency of residents' visits. We evaluated the CES of residential green spaces by assessing residents' satisfaction with these spaces in the city of Zhengzhou, China. The data reveal the supply capacity of CES in residential green spaces: the results suggest that the level of recreational services is low, whereas the residents' satisfaction with the sense of place and neighborhood relations is high. The lower the frequency of residents who visit a park outside the residential area, the higher the satisfaction with the CES. This suggests that residential green spaces can effectively compensate for the lack of nearby parks owing to their proximity to residents' living quarters. The CES in residential communities increased as vegetation coverage increased, indicating that natural vegetation is a source of CES. In addition, the results showed that residents' perceptions of plant decoration, landscape patterns, and management and infrastructure in particular can effectively improve the level of CES, and this could compensate for CES that have shrunk owing to low green space coverage. This study has practical significance and value for the planning and design of residential green spaces, offering suggestions for urban landscape planners and decision makers. Future research should combine the residents' perception of demand and supply of CES and should clarify the gap and trade-off between them.